Benthic habitats do show a significant latitudinal diversity gradient: A comment on Kinlock et al. (2018). Issue 11 (24th July 2019) - Menegotto, André; Kurtz, Márcia Neunschwander; Lana, Paulo da Cunha
Abstract: The latitudinal diversity gradient (LDG) has been investigated for decades, with hundreds of studies focusing on different organisms, regions and habitat types. Meta‐analysis may be considered, therefore, a useful tool to explore the generality and limitations of this remarkable macroecological pattern. The first meta‐analysis exploring variations in the LDG, published by Hillebrand in 2004, revealed that the latitudinal decline in species richness seems to be indeed a general phenomenon. However, Kinlock et al. (2018, Global Ecology and Biogeography, 27, 125–141) revisited recently the challenge of synthesizing individual LDGs and indicated that the phenomenon is not ubiquitous among habitats of the marine realm. More precisely, they indicated that the phenomenon is non‐significant in the benthic habitat. Here, we suggest that the marine habitat categories used by them (i.e., benthic, coral reefs, coastal, open ocean) are not independent and that reclassifying the studies significantly alters one of their main results. By assigning the studies into benthic and pelagic categories, and additionally into coastal or oceanic zones, we show that non‐ambiguous, evolutionarily meaningful marine habitats display a significant latitudinal decline in species richness.